Living Safe: A Self-management program for people with vision impairment - Packer, Tanya; Simpson, C.; Drury, Vicki; Sim. S.; Pereira, M.; Re, M. (Curtin University of Technology, 2009)
Living Safe is a self-defence self-management program for people with vision loss. The Living Safe manual includes all the materials necessary for a health professional to initiate and facilitate a six-session or two-day intensive course on crime prevention and psychological and physical self-defence strategies for people with vision loss. Step-by-step instructions for establishing the course and recruiting participants, as well as instructions for conducting an individual pre-screening interview are provided. The program is underpinned by the principles of self-management. The Living Safe program grew out of the seminal work of David, Kollmar, and McCall (1998) who pioneered the first program relating to self-defence and crime prevention for people with vision loss at the Center for the Visually Impaired in Atlanta. Living Safe builds on this work by adding to the content and embedding the principles of self-management into a structured program tailored for people with vision loss. This protocol provides people with the opportunity to learn, practise and choose techniques to protect and defend themselves physically and psychologically from potential dangers in the home, workplace and community. Although the program is adaptable globally it has been written in the context of Australian society.